Clinical trials: from problem child to the driving force of medical advancement - Delanerolle, G; Thayanandan, T; Riga, J; Griffiths, J; Lawson, J; Au-Yeung, S; Haque, N; Sandle, N; Raymont, V (Mark Allen Group, 2020)
Clinical trials are conducted to find better ways to prevent, screen for, diagnose or treat human disease. The development of clinical trials throughout history has built the foundation for ethically and scientifically robust research. As our healthcare needs have evolved, so have clinical trials and the standards by which they are run. Vanessa Raymont and colleagues explore the past, present and future of the clinical trial.